Identification and characterization of natural latex from tapioca (Manihot Esculenta) / Nor Syazwani Binti Mohd Sidek. - Nor Syazwani Mohd Sidek (School of Materials Engineering, Universiti Malaysia Perlis, 2014)
The main objective of this study is to identify and characterize the natural latex from tapioca (Manihot esculenta) as the potential alternative source of rubber tree Hevea brasiliensis.